(untitled) (IAHS Medical Journal, 2025)
Background: The Achilles tendon is the largest and strongest tendon in human body and is composed of the Gastrocnemius and the Soleus muscle to create a musculotendinous complex (Triceps Surae) that crosses the ankle and subtalar joint. It is then inserting primarily on the central middle portion of the posterior calcaneus as well as providing fibers that extend around the heel to blend in with the planter fascia. Achilles tendon is the most injured tendon of athletes in the lower extremities and has been noted to be the most common tendon to rupture spontaneously. The prevalence of Achilles tendinopathy is considerable in a variety of different sports, especially in runners and various ball sports. A ruptured Achilles tendon poses a difficult problem for treatment due to proximal retraction of the tendon. Surgical repair is the current treatment choice because of poor prognosis after conservative management. Many techniques are available for the surgical repair such as end-to-end suture, end-to-end suture with augmentation. Surgeons repair these injuries by different surgical technique in different centers of the country. Abraham and Pankovich techniques for spontenious rupture are applied in Institute of Applied Health Sciences (IAHS) Hospital Chattogram. This study was performed to evaluate the result of Abraham and Pankovich techniques for degenerative rupture of TA. Materials and methods: This was a prospective study. Twenty two patients with a degenerative tendo achilles tear were repaired using Abraham and Pankovich technique between May 2021 and January 2023 in IAHS Hospital. 4patients were lost to follow up. Ankle radiographs were obtained to rule out calcaneal fractures; patients with such fractures were excluded from the study. All patients underwent operative treatment after getting written informed consent. Functional outcome were assessed after 6 months of surgery. Results: Total 18 patients of degenerative rupture of TA were included for the study, 72% of them were male. Middle 3rd rupture were most common. All underwent surgery after proper evaluation and followed upto 6 months. Functional outcome with Activity Daily Living (ADL) were evaluated after that, 13 patient (72%) having excellent out come with painless walking without any support. One of the patient had SSI and one with skin slough out, both were treated in IAHS center accordingly. Conclusion: Results of reconstruction of Achilles tendon ruptures using Abraham and Pankovich techniques show a strong and stable repair that allows early weight bearing and ambulation with favorable clinical results in majority of patients. IAHS Medical Journal Vol 7(2), December 2024; 69-72